Pengaruh Penambahan Pasta Ubi Jalar Ungu (Ipomoea batatas var. Ayamurasaki) pada Es Krim Sinbiotik terhadap Jumlah Bakteri Asam Laktat, pH, dan Overrun - Sahbani, Lathifah Nur; Putranto, Wendry Setiyadi; Utama, Dicky Tri (Unpad Press, 2023)
Synbiotic ice cream is a functional food that consisting of probiotics and prebiotics. The addition of purple sweet potato paste can be utilized as a natural prebiotic source in making synbiotic ice cream. The aim of this research was to determine the effect of the addition of purple sweet potato paste in synbiotic ice cream on the number of lactic acid bacteria, pH, and overrun. This research was conducted experimentally using a completely randomized design with 4 concentration levels of purple sweet potato paste (0%, 5%, 10%, and 15%) and was repeated 5 times. The observed variables included the number of lactic acid bacteria, pH and overrun. The data obtained were analyzed using the one-way analysis of variance and Duncan’s multiple range test if the treatment showed a significant effect on the variables. The results showed that the addition of purple sweet potato paste had a significant effect (P<0.05) on the number of lactic acid bacteria and pH, but had no significant effect on the overrun. The addition of 10% purple sweet potato paste is preferred with a lactic acid bacteria count of 1.98 x 108CFU/mL, pH value of 4.77 and overrun of 14.23%.